Eppur, si muove - Le régime de sécurité européen - Les États non belligérants et la guerre en ex-Yougoslavie - Roussel, Stéphane; Portmann, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
The central assumption of this paper is that international regime theory constitutes an important heuristic tool which contributes to a better understanding of the dynamics of European security as it emerges from the Cold War era. Comprising a set of principles, norms, decision-making procedures and a framework of permanent organizations, the new European architecture forms an authentic security regime based on a process of regional cooperation. The Yugoslav conflict, which constitutes the first test of this regime, illustrates the fact that, even if these institutions failed to end the conflict, they did influence the behaviour of the main European actors. Not only did they favor interstate cooperation but they also reined-in the inclination of states to opt for self-centered policies based on short-term interests. From this perspective, regional security organizations have helped significantly to limit the scope and potential spill-over risks of the conflict in addition to decreasing the tension between the major European actors.